Adrenal androgens versus cortisol for primary aldosteronism subtype determination in adrenal venous sampling. (11th March 2022) - Viukari, Marianna; Kokko, Eeva; Pörsti, Ilkka; Leijon, Helena; Vesterinen, Tiina; Hinkka, Tero; Soinio, Minna; Schalin‐Jäntti, Camilla; Matikainen, Niina; Nevalainen, Pasi I.
Abstract: Objective: We examined if measurement of adrenal androgens adds to subtype diagnostics of primary aldosteronism (PA) under cosyntropin‐stimulated adrenal venous sampling (AVS). Design: A prospective pre‐specified secondary endpoint analysis of 49 patients with confirmed PA, of whom 29 underwent unilateral adrenalectomy with long‐term follow‐up. Methods: Concentrations of androstenedione, dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulphate (DHEAS) were measured during AVS in addition to aldosterone and cortisol. Subjects with lateralisation index (LI) of ≥4 were treated with unilateral adrenalectomy, and the immunohistochemical subtype was determined with CYP11B2 and CYP11B1 stains. The performance of adrenal androgens was evaluated by receiver operating characteristics (ROC) curve analyses in adrenalectomy and medical therapy groups. Results: During AVS, the correlations between cortisol and androstenedione, DHEA and DHEAS for LI and selectivity index (SI) were highly significant. The right and left side SIs for androstenedione and DHEA were higher ( p < .001) than for cortisol. In ROC analysis, the optimal LI cut‐off values for androstenedione, DHEA and DHEAS were 4.2, 4.5 and 4.6, respectively. The performance of these LIs for adrenal androgens did not differ from that of cortisol. Conclusions: Under cosyntropin‐stimulated AVS, the measurement of androstenedione and DHEA did not improve the cannulation selectivity. The performance of cortisol and adrenal androgens are confirmatory but not superior to cortisol‐based results in lateralisation diagnostics of PA.